Distributional Effects of Intergovernmental Transfers in Mexico - Carlos Rodriguez Castelan; Kiyomi Cadena; Laura Moreno Herrera (Institute of Labor Economics (IZA), 2020)
A rigorous understanding of the developmental effect of fiscal transfers to subnational governments remains an important policy research issue globally. This paper exploits a novel dataset of 20 years of municipal poverty maps and local public finances to study the effects on local welfare of a large fiscal transfer fund earmarked for social investment in more than 2,000 Mexican municipalities. Results show a positive but modest effect on the average household income, and positive effects on seven nonmonetary welfare measures. In contrast, these funds have no significant impact on extreme and moderate monetary poverty. These results provide important lessons for policy on the effects of earmarked funds to reduce territorial poverty and inequality in terms of incentives to design formulas to distribute earmarked fiscal resources to subnational governments.
Keywords: C26; D30; H72; H77; I3; 330; fiscal federalism; earmarked transfers; decentralization; poverty; Mexico